Web-Based Item Tracking System Using RFID - Azinurrachman Maulana; Siti Aisyah; Prasaja Wikanta (Jurnal Rekayasa Elektrika, 2023)
Numerous tools, kits, and other items are utilized daily by many individuals in the college laboratories. Without a proper inventory record, there is a risk of missing and misplacing some items. The system for tracking items using Radio Frequency Identification (RFID) accessed via the website has been designed to track the location of each item in the laboratory using RFID technology. The primary objective of this system is to monitor and record inventory. Information regarding the inventory is stored in a database, which can be accessed to track inventory and review the history of specific items via the Internet. The designed system is capable of tracking and managing laboratory equipment inventory using RFID, accessible through a web-based platform.